The charm of the ocean / Adlina Razali and Mazrul Azreen Aladin - Razali, Adlina; Aladin, Mazrul Azreen (Faculty of Art and Design, 2021)
Evening dress is also known as an evening gown. Worn by women, it’s also known as court dress based on its creation at royal courts, and has its origin in the 15th century with the rise of Burgundian courts and its fashionable and fashion-conscious ruler Philip the Good. Evening gowns are usually made of luxurious fabrics such as chiffon, velvet, satin, and organza. Therefore, silk also is a popular fabric that used to make an evening gown. The types of evening gown are ball gowns and evening gowns differ in that a ball gown will always have a full skirt and fitted bodice, while an evening gowns can be any silhouette such as mermaid, A-line, or a trumpet shaped and it also may have straps, halters or even sleeves. For the evening dress idea, Mystery of Atlantic Ocean was chosen as the subject matter and the collection named as “The Charm of The Ocean”. It is referring to how beautiful the ocean is. It's also to show people what else it’s happening in the ocean. The world is full of unsolved mysteries, and this reveals the history of the ocean and what is actually happening over there. There are three main points that I had to research, which is the Atlantic Ocean, Bermuda Triangle and Titanic. The design is inspired by the era in which mystery happens. Most of that design is inspired by the 1950s era which is full of layered, flare and ruffles. Royal blue is the main colour for these designs because it refers to the colour of the ocean. Satin matte fabric for these dresses were chosen because of the shining effect showing in the evening look. The next colour used is a darker shade of royal blue with chiffon georgette fabric to show the flowy of certain parts for this design. Besides that, light grey refers to the colour of the cloud. For the 1st design, a ball gown dresses inspired by an old trend in the Titanic era.